Muscle ultrasound imaging in the diagnosis of amyotrophic lateral sclerosis - Yu. N. Rushkevich; G. V. Zabrodets; S. A. Likhachev (Нервно-мышечные болезни, 2015)
Amyotrophic lateral sclerosis (ALS) is the most common form of motor neuron disease. This pathology is characterized by the involvement of central and peripheral motor neurons in the pathological process. One  f the specific symptoms of ALS is fasciculations - involuntary muscle contractions that may occasionally precede the development of muscle weakness and atrophies. This paper summarizes the accumulated practical experience in using muscle ultrasound study in the diagnosis of fasciculations and their prevalence as an early sign of anterior corneal lesion in ALS.